OSF/Motif programmer's reference, revision 1.0 (Englewood Cliffs, New Jersey : Prentice-Hall, 1990)
Low level user's guide for users of system, rather than for programmers. Largest potential market of 5 books.
[I.] Programmer's guide. [II.] Programmer's reference. [III.] Style guide. [IV.] User's guide.
Includes index.
Keywords: MOTIF (COMPUTER FILE)